Macro-ergonomics and musculoskeletal disorders (MSD) in multinational company / Nur Yusrina Abdullah - Nur Yusrina , Abdullah (2013)
Macro-ergonomics approach will lead to greater productivity, motivation and employee safety and health which regard to work related musculoskeletal disorder (WRMDs). This study is focusing on two elements of the macro-ergonomic approach which are management support and organizational safety culture towards ergonomics program. Effective ergonomics program at workplace is important in reducing the number of work related musculoskeletal disorders (WRMDs) in an organization. In this research study, the variables that influence the ergonomics program at workplace had been explored and analyzed. There are two (2) independent variables identified which are management support and organizational safety culture and one (1) dependent variable which is ergonomics program at workplace. Total of 207 sample sizes has been taken from various level groups that consist of management, professional (engineers), technicians, trainers and operators. Study survey has been conducted through random sampling. Quantitative survey has been used for this study. From analysis result it shows that five (5) hypotheses have been accepted. The result concludes that management support and organizational safety culture does exist in the sub organization and there was a good correlation in between management support and ergonomics program where r = 0.893, n = 207, p < 0.000. There is also correlation in between organizational safety culture and ergonomics program where r = 0.731, n = 207, p <0.000. Researcher had also revealed that management support had a positive relation with the organizational safety culture. It is believed that the effectiveness of the ergonomics program at workplace would reduce the number of work related musculoskeletal disorders (WRMDs) and it has been proven with the injury data obtained from the workplace study since last 5 years.